Market leadership through technology – Backward compatibility in the U.S. Handheld Video Game Industry - Jörg Claussen; Tobias Kretschmer; Thomas Spengler (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2012)
The introduction of a new product generation forces incumbents in network industries to rebuild their installed base to maintain an advantage over potential entrants. We study if backward compatibility moderates this process of rebuilding an installed base. Using a structural model of the U.S. market for handheld game consoles, we show that backward compatibility lets incumbents transfer network effects from the old generation to the new to some extent but that it also reduces supply of new software. We examine the tradeoff between technological progress and backward compatibility and find that backward compatibility matters less if there is a large technological leap between two generations. We subsequently use our results to assess the role of backward compatibility as a strategy to sustain market leadership.
urn:nbn:de:bvb:19-epub-12716-1
Keywords: 650